EXPOSIÇÃO CRÔNICA INTERMITENTE AO INSETICIDA CLORPIRIFÓS INDUZ REMODELAMENTO CARDÍACO, ASSOCIADO COM PREJUÍZO CARDIOVASCULAR E ESTRESSE OXIDATIVO EM RATOS - Minassa, Vitor Sampaio (2022)
Introduction: Chlorpyrifos (CPF) is an organophosphate pesticide (OP), banned in some countries due to its toxicity in humans, but that remains among the most used in the world. Clinical studies show that cardiovascular manifestations are commonly present